EFFECT OF LEVERAGE, CAPITAL STRUCTURE, RETURN ON ASSET, AND SALES GROWTH, ON THE PROFIT QUALITY OF CUSTOMER GOODS (FOOD AND BEVERAGE) COMPANIESLISTED ON THE INDONESIAN STOCK EXCHANGE 2019 - 2022) - Elisabeth Septia Sitanggang; Frince Gokma Simatupang; Nina Purnasari; Sondang Aida Silalahi (Journal Accounting International Mount Hope, 2024)
The development of this stock exchange is developing well even though the securities traded are generally bonds by Dutch companies and Indonesian government bonds through the Indonesian Development Bank. BEI helps companies to obtain additional capital by going public, namely the activity of offering shares or other securities carried out by issuers (companies that go public) to the public based on the procedures regulated by the Capital Markets Law and its Implementing Regulations. The type of research method used in this research is a quantitative research method. This research method is based on the philosophy of positivism. To research a particular population or sample, data collection uses research instruments, data analysis is carried out quantitative or statistical, with the aim of testing a predetermined hypothesis. Based on the results of the ANNOVA test above, the Fcount value is (6.948) and Ftable is (2.54). This means that 4.803 > 2.54 means Leverage, Capital Structure, Return on Assets, and Sales Growth together have a simultaneous effect on the Quality of Customer Company Profits. GOODS (Food & Beverage) which is listed on the Indonesian Stock Exchange